Pengaruh Penggunaan Model Pembelajaran Project Based Learning Terhadap Kemampuan Kognitif Pemecahan Masalah Pada Anak Usia Dini - Zami, Ilma Madya Khoiri Zam; Ruhiat, Dadang; Nugraha, Anggi Purwa (JOECE: Journal of Early Childhood Education, 2024)
This study aims to examine the impact of the Problem Based Learning (PBL) model on problem-solving abilities in early childhood, specifically for children aged 4-5 years. The research employed a quantitative method with a Pre-Experimental approach. Observation and documentation were used to collect data from 13 children at PAUD Kasih Ibu, Sindangrasa Village, Ciamis Regency. The results showed that 85% of the children were able to solve problems at an "excellent development" level, while 15% were in the "development as expected" category. The Wilcoxon test yielded a significance value of 0.001, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected, with a confidence level of 85%. These findings suggest that the PBL model is effective in enhancing problem-solving abilities in early childhood. This research contributes to supporting the use of PBL as a teaching strategy to develop the cognitive skills of children aged 4-5 years.